1993
DOI: 10.1099/0022-1317-74-6-1011
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of the predicted substrate-binding site of varicella-zoster virus thymidine kinase

Abstract: To investigate the mechanism of kinetic action and substrate recognition of varicella-zoster virus (VZV) thymidine kinase (TK), we designed and isolated a sitedirected mutant VZV TK which has double amino acid substitutions, 136threonine to leucine and la7isoleucine to leucine (SDM TK). This mutant was designed to alter the substrate-binding site of the VZV TK to duplicate that of the herpes simplex virus type 2 enzyme. Kinetic studies of the activity of wild-type TK indicated that the binding order of ATP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…ACV and BV-araU are phosphorylated by VZV TK (1,23), but the affinities between these nucleosides and VZV TK are quite different. The K i value of ACV for VZV TK is Ͼ500 M, and that of BV-araU is 0.26 M (17). Moreover, the affinities of these nucleoside triphosphates for cellular DNA polymerase also differ, and the K i values of ACV triphosphate and BV-araU triphosphate are 2.1 M (6) and 0.007 to 0.14 M (14), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…ACV and BV-araU are phosphorylated by VZV TK (1,23), but the affinities between these nucleosides and VZV TK are quite different. The K i value of ACV for VZV TK is Ͼ500 M, and that of BV-araU is 0.26 M (17). Moreover, the affinities of these nucleoside triphosphates for cellular DNA polymerase also differ, and the K i values of ACV triphosphate and BV-araU triphosphate are 2.1 M (6) and 0.007 to 0.14 M (14), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…TKs from herpes viruses comprise a third group of dNKs with amino acid sequences and overall structures more closely related to the enzymes of the non-TK1-like family 60,98,[109][110][111][112] Dual TKand TMPK activity is a special feature of most herpes viruses TKs. [112][113][114][115] Recent crystallographic studies with BaTK and BcTK, having 96% amino acid sequence identity, 99 have shown that depending on the presence or absence of the endogenous substrate, Thd, in the substrate binding pocket, TK1-like enzymes exist in a closed and a more open form (Fig. 4).…”
Section: Tk1-like Enzymesmentioning
confidence: 99%
“…The thymidine K m value for wild-type VZVTK used as a reference was 1.96 M (Table 1) compared with literature K m values of between 0.3 and 0.6 M (Suzutani et al, 1993;Amrhein et al, 2000). Whereas our K m value was greater than the average, VZVTK wildtype and mutants were purified, and their activity was as- (Table 1), with the R84V thymidine kinase mutant showing the weakest apparent affinity (9.1 Ϯ 1.5 M).…”
Section: Resultsmentioning
confidence: 99%
“…The previously reported site-directed mutagenesis of residues making direct contact with the thymidine pyrimidine ring invariably led to almost complete loss of enzyme activity, even when substituting HSV1TK residues into VZVTK (Roberts et al, 1991;Suzutani et al, 1993). Because it was necessary to retain significant enzyme activity, we tried a more subtle approach.…”
mentioning
confidence: 99%